2020
DOI: 10.3389/fpls.2020.00729
|View full text |Cite
|
Sign up to set email alerts
|

Insights Into Chloroplast Genome Evolution Across Opuntioideae (Cactaceae) Reveals Robust Yet Sometimes Conflicting Phylogenetic Topologies

Abstract: Plastome Evolution in Opuntioideae (Cactaceae) with primers designed for continued evolutionary studies across Cactaceae. These results bring new insights into the evolution of plastomes in cacti, suggesting that further analyses should be carried out to address how ecological drivers, physiological constraints and morphological traits of cacti may be related with the common rearrangements in plastomes that have been reported across the family.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 163 publications
(253 reference statements)
2
49
0
Order By: Relevance
“…Whole genomic DNAs of all taxa were extracted using a standard CTAB protocol with silica column cleaning (see Majure et al 2019;Köhler et al 2020). DNAs were resuspended in 300 ul of TE (Tris-EDTA) buffer (pH 8.0), and DNA quantity was analyzed on a Qubit 2.0 Fluorometer.…”
Section: Methodsmentioning
confidence: 99%
“…Whole genomic DNAs of all taxa were extracted using a standard CTAB protocol with silica column cleaning (see Majure et al 2019;Köhler et al 2020). DNAs were resuspended in 300 ul of TE (Tris-EDTA) buffer (pH 8.0), and DNA quantity was analyzed on a Qubit 2.0 Fluorometer.…”
Section: Methodsmentioning
confidence: 99%
“…The best fit k-mer of 45 was selected for use in a subsequent analysis of the genomes. The quality of the newly assembled genomes was evaluated on read level basis by aligning the trimmed raw reads to the de novo assemblies using Geneious mapper, Geneious version 9.1.4 ( Kearse et al, 2012 ) with medium- to low-sensitivity option and iteration up to five times ( Köhler et al, 2020 ). Gene annotation was conducted using Plastid Genome Annotator (PGA) ( Qu et al, 2019 ) with an annotated plastome Amborella trichopoda (GenBank accession no.…”
Section: Methodsmentioning
confidence: 99%
“…All whole genomic DNAs were sent to Rapid Genomics LLC (Gainesville, FL, USA) for library preparation and sequencing using a genome skimming approach (Straub et al, 2012) on the Illumina HiSeq X Ten platform using paired‐end, 150‐bp reads. Genome skimming refers to shallow sequencing of whole‐genomic DNA, which preferentially retrieves high copy‐number portions of genomes and is thus efficient for sequencing nrDNA and plastome fractions of whole genomic DNA (see Majure et al, 2019, 2021a; Köhler et al, 2020, for the use of genome skimming in Cactaceae). Raw reads used in our plastome and ETS/ITS assemblies from all newly sequenced taxa for this study (see Appendix 1) were deposited in the NCBI Sequence Read Archive under Bioproject PRJNA650542 (https://www.ncbi.nlm.nih.gov/sra/PRJNA650542).…”
Section: Methodsmentioning
confidence: 99%
“…However, further work in other clades within Opuntioideae has revealed similar topological incongruences between plastid and ITS data (Ritz et al, 2012; L. C. Majure et al, unpublished manuscript), especially at deeper phylogenetic levels, suggesting that either paralogy or homoplasy may play a role in those poorly supported incongruences based on ITS data in Cactaceae. More recent work using plastome data has shown that Consolea was likely sister to the rest of Opuntieae (Köhler et al, 2020).…”
Section: Figurementioning
confidence: 99%